PENAMBAHAN KINESIOTAPING PADA LATIHAN QUADRICEPS SETTING MENINGKATKAN KEMAMPUAN FUNGSIONAL PENDERITA OSTEOARTHRITIS SENDI LUTUT - Eko Wibowo; J. Alex Pangkahila; S. Indra Lesmana; Nengah Sandi; I Putu Adiartha Griadhi; Sugijanto - (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Osteoarthritis of the knee joint is a chronic degenerative joint disease, with slowly progressive runs, where the structure of joints have a pathological changes. Characterized by imbalances of regeneration and degeneration that causes pain, impaired joint mobility or limited range of motion (LGS), stiffness, instability and muscles weakness arround the joint. The purpose of this study was to compare functional ability level in the additional kinesiotaping for quadriceps setting exercise in patients with osteoarthritis of the knee joint. This research uses experimental methode with pre-test and post-test group design. Number of samples of the first group 9 patients were given quadriceps setting exercise with a duration of 3 sets, 10 repetitions, three times a week for 3 weeks, in second group were 9 patients given kinesiotaping combine with quadriceps setting with 3-days used and 2-day intervals. The results showed : (1) there is an increase functional ability test results in the treatment group I. Related t-test results show mean ± SB pre test (28.18 ± 2.84) and the mean ± SB post test (31.41 ± 3.31) with p = 0.000 (p <0.05). (2) there is increased functional ability test results in the treatment group II. Results related t-test showed mean ± SB pre test (26.48 ± 3.74) and (31.30 ± 3.33) with p = 0.000 (p <0.05). (3) there are significant differences in test results koos in the treatment group I and group II treatment. Comparison test results show mean ± SB group I (3.22 ± 1.65) and the mean ± SB group II (4.82 ± 1.12) with p = 0.003 (p> 0.05). It was concluded that the addition kinesiotaping the quadriceps setting exercise can improve functional ability of patients with osteoarthritis of the knee joint. There is a significant difference in functional enhancement between the quadriceps setting treatment and the addition of kinesiotaping to the quadriceps setting exercise. The addition of kinesiotaping to the quadriceps setting exercise is better than the quadricep setting exercise to improve functional ability in patients with knee osteoarthritis.